Common Fixed Point Theorems for Contractive Mappings of Integral Type in G-Metric Spaces and Applications. (31st January 2021) - Zhang, Fengrong; Zhang, Xiangshuai; Hao, Yan
Abstract : Two common fixed point theorems for weakly compatible mappings satisfying contractive conditions of integral type in G -metric spaces are demonstrated. The results obtained in this paper generalize and differ from a few results in the literature and are used to prove the existence and uniqueness of common bounded and continuous solutions for certain functional equations and nonlinear Volterra integral equations. A nontrivial example is included.